Examination malpractice: a stigma on school effectiveness in Nigeria (2004)
The paper opens with the meaning of school effectiveness and the need for examination as a method of assessment of students who have gone through one level of education or the other. It discusses the incidence of examination malpractice in Nigeria, as well as prevalence and forms. The paper concludes with a discussion of efforts made so far in curbing examination malpractice in Nigeria and the examination malpracices decree 33 of 1999.